2009
DOI: 10.1016/j.ajhg.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Genotype Calling and Haplotype Phasing Improves Genotype Accuracy and Reduces False-Positive Associations for Genome-wide Association Studies

Abstract: We present a novel method for simultaneous genotype calling and haplotype-phase inference. Our method employs the computationally efficient BEAGLE haplotype-frequency model, which can be applied to large-scale studies with millions of markers and thousands of samples. We compare genotype calls made with our method to genotype calls made with the BIRDSEED, CHIAMO, GenCall, and ILLUMINUS genotype-calling methods, using genotype data from the Illumina 550K and Affymetrix 500K arrays. We show that our method has h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
176
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(182 citation statements)
references
References 37 publications
(60 reference statements)
2
176
0
Order By: Relevance
“…As expected, we have found that excluding sites with low estimated r 2 results in higher quality sets of SNP calls (Browning and Yu 2009;Li et al 2010b). For example, in the original calls for the 1000 Genomes CEU sample, focusing on sites with r 2 greater than 0.0, 0.3, and 0.5 increases the ratio of transition to transversion SNPs from 1.86 to 1.88 and then to 1.97, excluding 0%, 5%, and 17% of the initial set of SNPs.…”
Section: Design Of Sequence-based Association Studiessupporting
confidence: 53%
See 1 more Smart Citation
“…As expected, we have found that excluding sites with low estimated r 2 results in higher quality sets of SNP calls (Browning and Yu 2009;Li et al 2010b). For example, in the original calls for the 1000 Genomes CEU sample, focusing on sites with r 2 greater than 0.0, 0.3, and 0.5 increases the ratio of transition to transversion SNPs from 1.86 to 1.88 and then to 1.97, excluding 0%, 5%, and 17% of the initial set of SNPs.…”
Section: Design Of Sequence-based Association Studiessupporting
confidence: 53%
“…Using simulations, we evaluate the trade-offs involved in deep sequencing of a few individuals and shallower sequencing of larger numbers of individuals. We also discuss several other existing methods that can perform genotype calling from low-coverage sequence data (Browning and Yu 2009;Le and Durbin 2010;McKenna et al 2010). More importantly, we systematically compare study designs based on genotyping of tagSNPs, sequencing of many individuals at depths ranging between 23 and 303 and imputation of variants discovered by sequencing in a subset of individuals into the remainder of the sample.…”
mentioning
confidence: 99%
“…For example, the LD model can be incorporated into simulation methods used to generate empirical p-values in, for instance, methods to detect identity by descent from dense SNP data (Thomas, 2007;Thomas et al, 2008). They can also be used for imputation across SNP genotyping platforms, similar to the BeagleCall software (Browning and Yu, 2009). A final advantage of our general graphical modeling approach is its straightforward extension to include discrete covariates, such as an individual's population of origin, and outcome variables, facilitating, for instance, the detection of phenotype-haplotype associations, while controlling for population stratification.…”
Section: Discussionmentioning
confidence: 99%
“…GotCloud uses two tools for genotype refinement: Beagle (Browning and Yu 2009) and ThunderVCF . Beagle is computationally efficient, but the resulting haplotypes can be made more accurate by additionally running ThunderVCF, which is based on a model used by MaCH (Li et al 2010).…”
Section: Haplotype-aware Genotype Refinementmentioning
confidence: 99%